Coronary artery bypass grafting in a renal transplant patient: case report - Atılgan, Kıvanç; Demirdaş, Ertan; Boran, Mediha; Er, Zafer Cengiz; Çiçekçioğlu, Ferit (The European Research Journal, 2019)
The patients with end-stage renal disease have an increased risk of atherosclerosis and the probability of cardiovascular diseases. Due to the use of immunosuppressive agents, the patients having renal graft carry an additional risk of atherosclerosis or endocarditis. A 67-year-old male patient with a history of renal transplantation was referred to our hospital with a severe chest pain and dyspnea. After diagnosing severe ischemic coronary artery disease by coronary angiography, the patient underwent a successful operation of a single vessel coronary artery bypass grafting (CABG) in beating heart. Up to 20% of post-renal transplantation mortality is attributed to cardiovascular diseases. Graft rejection, the need of hemodialysis, perioperative infection are some of the major complications for renal transplant patients undergoing CABG surgery. Off-pump CABG (OPCABG) surgery is a less invasive technique in comparison with CABG with cardiopulmonary bypass (CPB), and protects the patient from negative effects of CPB such as complement system activation, inflammatory mediator secretion, thrombocytopenia, clotting disorders. We recommend to prefer OPCABG and have preoperative prophylaxis in order to avoid both perioperative infection and renal graft rejection in renal transplant patients undergoing CABG surgery.